The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsanm.2c04849
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfide-Induced Synthesis of Coral-Like MoS2/NiS2 Nanostructures for Overall Water Splitting

Abstract: The development of multifunctional electrocatalysts with rich resources, excellent performance, and stability is necessary for water splitting to achieve sustainable hydrogen and oxygen production. Herein, we report the preparation of a bifunctional coral-like nanostructured electrocatalyst (p-MoS2/NiS2) by in situ vulcanization of polymeric sulfur with a MoO3/Ni as the precursor. It is exciting that the whole preparation process of the electrocatalyst can be completed in a few hours. The as-fabricated multime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…9H5E-CF 9H5E-CC showed high stability with negligible voltage change. Additionally, compared with the reported bifunctional catalysts for HER, OER, and overall water splitting in alkaline electrolytes, a competitive overpotential of 142 mV (η 10 ) for HER, 294 mV (η 50 ) for OER, and 1.88 V (at 50 mA cm −2 ) for overall water splitting were achieved for the MoO 3 -NiS x catalyst, as shown in Table S4 [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9H5E-CF 9H5E-CC showed high stability with negligible voltage change. Additionally, compared with the reported bifunctional catalysts for HER, OER, and overall water splitting in alkaline electrolytes, a competitive overpotential of 142 mV (η 10 ) for HER, 294 mV (η 50 ) for OER, and 1.88 V (at 50 mA cm −2 ) for overall water splitting were achieved for the MoO 3 -NiS x catalyst, as shown in Table S4 [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/catal13111426/s1, Figure S1 S1: Listing of the experimental parameters for fabricating the samples; Table S2: R s and R ct values of 9H5E-CC, 9H-CC, and 9H15-CC; Table S3: R s and R ct values of 9H5E-CF, 9H-CF, and 9H15-CF; Table S4: Comparison of the water splitting performance of the catalyst in this study with that of other reported bifunctional catalysts in 1 M KOH. References [39][40][41][42][43][44][45][46][47][48][49][50][51] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…37,38 Constructing a heterojunction between MoS 2 and other catalysts is a highly effective strategy to enhance the electrocatalytic performance of OWS. 39,40 The formation of a heterojunction induces band bending at the interface due to differences in Fermi energy levels, resulting in electron redistribution and the creation of an intrinsic electric field. This contributes to the acceleration of electron migration between interfaces and the formation of new active sites.…”
Section: Introductionmentioning
confidence: 99%